Bringing the Mechanistic Approach Back to Life: A Systematic Review of the Experimental Evidence for Coexistence and Four of Its Classical Mechanisms - Hawlena, Hadas; Garrido, Mario; Cohen, Carmit; Halle, Snir; Cohen, Shahar (Frontiers in Ecology and Evolution, 2022)
Coexistence theories develop rapidly at the ecology forefront suffering from interdisciplinary gaps and a lack of universality. The modern coexistence theory (MCT) was developed to address these deficiencies by formulating the universal conditions for coexistence. However, despite this theory’s mechanistic foundation, initially, it has only rarely been used to determine the exact mechanisms that govern the competitive outcome. Recent theoretical developments have made MCT more accessible to experimentalists, but they can be challenging in practice. We propose that a comprehensive understanding of species co-occurrence patterns in nature can be reached by complementing the phenomenological approach with both the mechanistic view of MCT and coexistence experiments of the type that prevailed from the 1970s to the 2010s, which focused on specific mechanisms (designated the “mechanistic approach”). As a first step in this direction, we conducted a systematic review of the literature from 19672020, covering mechanistic experiments for invasibility—the criterion for species coexistence—and the best-studied classical coexistence mechanisms, namely, resource-ratio, natural enemy partitioning, frequency-dependent exploitation by generalist enemies, and the storage effect. The goals of the review were to evaluate (i) the percentage of the abovementioned mechanistic experiments that satisfy the theoretical criteria (designated “eligible studies”), (ii) the scope of these eligible studies, and (iii) their level of support for the theoretical predictions, and to identify their (iv) overarching implications and (v) research gaps. Through examination of 2510 publications, the review reveals that almost 50 years after the theoretical formulations of the above four coexistence mechanisms, we still lack sufficient evidence to reveal the prevalence of coexistence and of each of the coexistence mechanisms, and to assess the dependency of the mechanisms on the natural history of the competing organisms. By highlighting, on the one hand, the overarching implications of the mechanistic approach to coexistence, and on the other hand, current research gaps, and by offering ways to bridge these gaps in the future, we seek to bring the mechanistic approach back to life.